The Impact of Reward, Punishment, Training and Competency Systems against the Performance of Aviation Security Officers - Nada Majid, Hanif; Dewi Kusumayati, Lusiana; Indrianto Sudjoko, Rifdian (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sultan Hasanuddin International Airport Makassar is one of the main gateways of air transportation in eastern Indonesia serving domestic and international routes. With quality human resources, it will improve excellent performance to support comfort and safety in flight. This study aims to determine the effect of the reward, punishment, training and competency system on the performance of Aviation Security officers. This research method uses quantitative, which describes the circumstances that are happening to the object of research. Data collection techniques are carried out by distributing questionnaires, observations and documentation. In the sampling of this study as many as 40 respondents consisting of 10 respondents, supervisors, Aviation Security officers and 30 Aviation security officers. The data analysis technique in this study uses the Statistical Package for the Social Science (SPSS). The results of the study showed that the significant value of the results obtained t count amounted to 2.834 greater than t table (1.68385), the results of multiple linear regression tests showed a constant value of 10.478 positive. This means that there is a positive and significant influence between the reward, punishment, training, and competency systems on the performance of Aviation Security officers. It was concluded that if the system of reward, punishment, training, and competence provided increases, then the performance of Aviation Security officers will also increase.